Case report: Diagnosis and treatment of pulmonary choristoma in a newborn calf - Usaki, Noriyo; Tsuka, Takeshi; Hatanaka, Midori; Sunden, Yuji; Imamura, Aoi; Morita, Takehito (Frontiers in Veterinary Science, 2024)
A 4-day-old female Holstein calf presented with a large-sized, protruding mass in its back, at birth. Radiography identified the deformed spinous process in the second and third lumbar vertebras, suggesting spina bifida. Ultrasonography of the back mass revealed anechoic bronchi-like structures and large vessels with rich blood flow running parallel within the homogenous echogenic mass’s parenchyma. Doppler ultrasonography also revealed pulsatile vessels entering into the deeper side of the transverse process of the lumbar vertebras at the right-sided base of the protruding mass. These imaging results were helpful for surgical planning, in which a large arterial vessel was sutured at the right-sided mass’s base, followed by resection of the mass itself. The mass’s resection could be carried out according to the planned surgical procedure, though its invasion was too deep to be resected completely. Histopathology for the resected specimens revealed that the mass mainly had lung-tissue-like structures comprised of bronchi-, bronchiole- and alveoli-like structures, and large vessels, allowing the diagnosis of pulmonary choristoma. Doppler ultrasonography could contribute to the differentiation between the bronchi-like tubular structure and the large arterial vessels on the same images, aiding diagnosis of this disease.